(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Tobacco use in Bangladesh has been high, but there is no report on community-level intervention to reduce tobacco use. The aim of this article is to report the experience of eight years of community intervention to reduce tobacco use in a rural area of Bangladesh. We have done four householdbased surveys (2006, 2008, 2012, and 2014) in Ekhlaspur village of Chandpur district. One man and one woman aged ≥18 years from each of 600 households were selected for each survey randomly to monitor tobacco use in this village concomitant with community interventions. The intervention package included yard meetings, health facility-based counselling, observance of the world no-tobacco days, and periodic lectures in schools. Chi-square for linear trend analysis was done to examine declining trends of prevalence of tobacco use. There were 953 to 1015 participants, approximately half being men in each survey. Their mean age was 44 to 45 years in all surveys. A decline in tobacco use has been observed from 58.8 in 2006 to 43.4% in 2014 (Ptrend=0.000). There has not been any perceivable change in smoking in women because it was either zero or close to zero across surveys. A similar trend was observed in age groups, educational achievements, and hypertension (Ptrend=0.000). Smoking in men declined from 58.3 to 35.2% (Ptrend= 0.000). Community interventions in a sustainable manner can reduce tobacco use in rural communities of Bangladesh. BSMMU J 2022; 15(3): 157-161